Drugs and renal insufficiency - Aronson, J (2007)
Renal insufficiency alters both the disposition of drugs in the body (pharmacokinetics) and tissue responses to drugs (pharmacodynamics). If drugs or their active metabolites are excreted by the kidneys they can accumulate in renal insufficiency and cause adverse effects. Using simple principles, one can calculate changes in drug dosages that are required in renal insufficiency. Usually it is necessary to change only the maintenance dosage; however, occasionally loading doses are also affected. Drugs with which special care must be taken are those with a low therapeutic index (for example, digoxin, aminoglycoside antibiotics, lithium). Renal replacement therapy can also alter the rate of elimination of a drug and dosages may have to be altered. In some cases the response to a drug is changed in renal insufficiency; dosages should be reduced or the drug avoided altogether, since it is impossible to predict appropriate changes in drug dosages. Nephrotoxic drugs cause renal damage by many different mechanisms and can affect the dosages of other drugs. © 2007.